Place Identity Strategies at University Constructed by Minority Arab-Israeli Student Groups - Billig, Miriam (Frontiers in Psychology, 2021)
The study examines place identity of minority group Arab-Israeli students studying at a campus affiliated by the Israeli hegemonic majority, against the backdrop of the enduring Israeli-Palestinian conflict. The study analyzes place identity construction strategies utilized by these students, and the formation patterns of the new place identity reflected in everyday campus life. Students' subjective experiences were revealed through ethnographic and qualitative phenomenological methodology and in-depth interviews. From the findings it became apparent that life under conditions of ongoing ethnic-political conflict forces minority groups to develop strategies regarding their place identity. These strategies are fluidly employed depending on the specific context of time and place. Four place identity strategies were identified: overt, borrowed, avoidant and ideological. Key factors contributing to the construction of each strategy were discovered: rooted place identity; gender expectations, and proactive or passive attitude to place. Implementation tactics such as individual versus collective approaches, distancing from other groups, and the flow between multiple identities were also uncovered. The study asserts that the strategies, tactics, and key factors revealed in the research contribute to place identity theory, and will enrich other place identity studies of minority groups and communities in fluid contexts. Expanding theoretical discourse with respect to the strategies and tactics of place identity could promote opportunity for integration and co-existence.